Оптимизационный подход к выбору параметров линейного импульсного индукционного электромеханического преобразователя - Болюх, Владимир Федорович; Щукин, Игорь Сергеевич (Національний технічний університет "Харківський політехнічний інститут", 2018)
Разработан оптимизационный подход к выбору параметров линейного импульсного индукционного электромеханического преобразователя (ЛИИЭП) с многовитковым короткозамкнутым якорем. Он состоит в нахождении максимума интегрального критерия эффективности, учитывающего максимальную скорость и КПД преобразователя скоростного назначения, амплитуду и импульс электродинамических усилий в преобразователе силового назначения при минимальных превышениях температур, массе активных элементов и токе индуктора. При этом используется цепная математическая модель, которая учитывает взаимосвязанные электрические, магнитные, тепловые и механические процессы ЛИИЭП. Разработана методика поиска максимума интегрального критерия эффективности ЛИИЭП в поисковом пространстве с использованием глобального и локального методов оптимизации. В качестве глобального метода используются генетические алгоритмы, а в качестве локального – метод Нелдера-Мида. Установлены электрические параметры емкостного накопителя энергии и геометрические параметры ЛИИЭП, обеспечивающие наибольшие значения интегрального критерия эффективности в зависимости от принятого варианта стратегии оценки эффективности. В оптимизированных преобразователях скоростного и силового назначения интегральные критерии эффективности в среднем в 2,2 раза выше, чем в ЛИИЭП основного исполнения.

Purpose. The purpose of the paper is to select the main parameters of the linear pulse induction electromechanical converters (LPIEC) for high-speed and power use with the use of the optimization approach, which provides an increase in speed and power indicators with limited electric, thermal and mass-dimensions. Methodology. A technique for finding the maximum of the integral efficiency criterion of LPIEC in the search space using a global optimization method that randomly searches for parameters, preventing entry into a local maximum, and a local method ensuring the contraction ofthe range of parameters with a global maximum to minimum dimensions is developed. As a global optimization method, genetic algorithms are used, and the Nelder-Mead method is used as the local method. Results. The LPIEC inductor should have a maximum external and minimum internal diameter, and its height should be less than that of the LPIEC of the basic design. The armature should have a maximum outer diameter, and the thickness of its wire should be minimal. The armature should be made with a significantly higher height, a greater number of turns and a wider wire. The height of the LPIEC inductor for power purposes should be almost the same as that of the LPIEC of the basic design. In this case, the number of turns of the inductor and the cross section of its wire should be approximately the same. The armature should be made with a slightly larger inner diameter and a significantly higher height. This armature should have a larger number of turns of wire, which must be stacked in 4 layers, and a large width of the wire. The average energy value and voltage of the capacitive energy storage for the LPIEC for high-speed and power applications should be higher than for the LPIEC of the basic design. Originality. An optimization approach to the choice of LPIEC parameters witha multi-turn squirrel arm is developed, which consists in finding the maximum of an integral efficiency criterion that takes into account the maximum speed and efficiency in a high-speed converter, the amplitude and magnitude of the electrodynamic force pulse in a power converter, with minimum temperature excesses, the mass of active elements and current of the inductor. The optimization uses a chain mathematical model that takes into account the interconnected electrical, magnetic, thermal and mechanical processes of the LPIEC. Practical value. The electric parameters of the capacitive energy storage device and the geometric parameters of the LPIEC are determined, which ensure the largest values of the integral efficiency criterion depending on the adopted version of the efficiency evaluation strategy. In optimized speed and power transfer converters, the integral efficiency criteria are 2.2 times higher on average than in the basic performance of the LPIEC.
An optimization approach to the choice of parameters of linear pulse induction electromechanical converter
Keywords: цепная математическая модель; интегральный критерий эффективности; оптимизационный подход; генетические алгоритмы; метод Нелдера-Мида; linear pulse induction electromechanical converter; chain mathematical model; integral efficiency criterion; optimization approach; genetic algorithms; Nelder-Mead method